2021
DOI: 10.3390/ijms22042121
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Gut Microbiota by Overnutrition Impact Gluconeogenic Gene Expression and Insulin Signaling

Abstract: A high-fat, Western-style diet is an important predisposing factor for the onset of type 2 diabetes and obesity. It causes changes in gut microbial profile, reduction of microbial diversity, and the impairment of the intestinal barrier, leading to increased serum lipopolysaccharide (endotoxin) levels. Elevated lipopolysaccharide (LPS) induces acetyltransferase P300 both in the nucleus and cytoplasm of liver hepatocytes through the activation of the IRE1-XBP1 pathway in the endoplasmic reticulum stress. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 128 publications
(159 reference statements)
1
14
0
Order By: Relevance
“…It is possible that this relative increase in our model may be secondary to increased mucus production, which is stimulated by LPS and inflammatory cytokines [68]. Overnutrition is known to increase plasma LPS through altered intestinal barrier permeability [69]. A prolonged period of overnutrition with a Western diet may have produced sustained endotoxemia and a secondary increase in intestinal mucus.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this relative increase in our model may be secondary to increased mucus production, which is stimulated by LPS and inflammatory cytokines [68]. Overnutrition is known to increase plasma LPS through altered intestinal barrier permeability [69]. A prolonged period of overnutrition with a Western diet may have produced sustained endotoxemia and a secondary increase in intestinal mucus.…”
Section: Discussionmentioning
confidence: 99%
“…Increased bacterial lipopolysaccharide (LPS) leakage from the gut into circulation and its initiated low-grade of inflammation play important roles in the development of insulin resistance in obesity and T2D (3,(32)(33)(34). We found that LPS can induce P300 in hepatocytes via reduction of the ubiquitination and degradation of P300, and elevated P300 impairs insulin signaling by acetylating IRS1 and 2 (27,35). Of note, P300 is a big protein, however, this protein has a relatively short half-life (5 h) (36), indicating that continuous protein translation in the cytoplasm is required to maintain the cellular P300 protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Bacteroidetes may have the potential to regulate atherosclerosis progression [ 30 ]. Moreover, lipid A of LPS from Bacteroides is an antagonist of immune stimulation and inflammatory cytokine response [ 31 , 40 ]. Furthermore, the study demonstrated an increase in the prominent bacterial families producing indole, i.e., Enterobacteriaceae , Clostridiaceae , and Verrucomicrobiace in CAD patients, which although statistically insignificant, was correlated with an increased indoxyl level which was twice as high as in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%